Peran Orang Tua Dan Guru Dalam Meningkatkan Minat Baca Siswa Sd - Liu Frederikus (Jurnal Sultra Elementary School, 2023)
Children's reading interest at the Elementary School (SD) level is one of the important indicators in their academic and social development. This study aims to explore the role of parents and teachers in increasing students' reading interest. The method used is a literature study by collecting data from various relevant sources. The results of the study show that parents act as role models, providers of reading facilities, and controllers of learning time, while teachers function as facilitators, motivators, and creative teachers. In addition, supporting factors such as the availability of books and good communication between parents and teachers greatly influence children's reading interest. Conversely, low parental awareness and an unsupportive environment are obstacles. This study concludes that collaboration between parents and teachers is very important to increase children's reading interest in elementary school, which ultimately has a positive impact on their academic achievement.